Analisis Lingkungan dan Metode Pembelajaran Di Taman Kanak-kanak An-Nur dalam Perspektif Teori Perkembangan Anak - Nasyafa Ira Ristian; Selvina Safira Ros; Ahmad Habib Rizwan; Aulia Wildanum Mukholadun; M. Bahri Mustofa (Institut Agama Islam Tarbiyatut Tholabah, 2026)
The learning environment and teaching methods have a significant impact on early childhood development. In practice, learning methods in kindergarten are still considered inadequate for the characteristics of child growth. The purpose of this study was to examine the learning environment and teaching practices at An-Nur Kindergarten through the lens of child development theory. This study used a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results showed that the learning environment at An-Nur Kindergarten was very good, with clean classroom facilities, a calm learning atmosphere, and positive interactions between teachers and students. However, the learning methods applied still tended to be simple and dominated by writing activities on the blackboard so that children's active participation in the learning process had not developed optimally. According to Jean Piaget's cognitive development hypothesis, early infancy is in the preoperational stage, which means that more concrete experiences, play activities, and exploratory learning are needed. Furthermore, Lev Vygotsky's Zone of Proximal Growth theory highlights the need for social contact, support (scaffolding), and active teacher participation in encouraging child growth. This study concluded that the learning environment at An-Nur Kindergarten has supported the learning process; However, more diverse, interactive learning methods that are appropriate to the developmental needs of early childhood need to be developed so that the learning process becomes more effective and meaningful.